K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1) Ta có: \(\left(x+5\right)\left(x+2\right)-3\left(4x-3\right)=\left(5-x\right)^2\)

\(\Leftrightarrow x^2+2x+5x+10-12x+9=25-10x+x^2\)

\(\Leftrightarrow x^2-5x+19-25+10x-x^2=0\)

\(\Leftrightarrow5x-6=0\)

\(\Leftrightarrow5x=6\)

\(\Leftrightarrow x=\frac{6}{5}\)

Vậy: \(x=\frac{6}{5}\)

2) Ta có: \(\left(x+2\right)^3-\left(x-2\right)^3=12x\left(x-1\right)-8\)

\(\Leftrightarrow x^3+6x^2+12x+8-\left(x^3-6x^2+12x-8\right)=12x^2-12x-8\)

\(\Leftrightarrow x^3+6x^2+12x+8-x^3+6x^2-12x+8-12x^2+12x+8=0\)

\(\Leftrightarrow12x+24=0\)

\(\Leftrightarrow12x=-24\)

\(\Leftrightarrow x=-2\)

Vậy: x=-2

3) Ta có: \(3x\left(12x-4\right)-9x\left(4x-3\right)=30\)

\(\Leftrightarrow36x^2-12x-36x^2+27x-30=0\)

\(\Leftrightarrow15x-30=0\)

\(\Leftrightarrow15x=30\)

\(\Leftrightarrow x=2\)

Vậy: x=2

4) Ta có: \(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)

\(\Leftrightarrow48x^2-12x-20x+5+3x-48x^2-7+112x-81=0\)

\(\Leftrightarrow83x-83=0\)

\(\Leftrightarrow83x=83\)

\(\Leftrightarrow x=1\)

Vậy: x=1

8 tháng 1 2020

a) 9x2 - 1 = (3x + 1)(2x - 3)

=> 9x2 - 1 = 6x2 - 9x + 2x - 3

=> 9x2 - 6x2 + 7x - 1 + 3 = 0

=> 3x2 + 7x + 2 = 0

=> 3x2 + 6x + x + 2 = 0

=> 3x(x + 2) + (x + 2) = 0

=> (3x + 1)(x + 2) = 0

=>\(\orbr{\begin{cases}3x+1=0\\x+2=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=-\frac{1}{3}\\x=-2\end{cases}}\)

b) 2(9x2 + 6x + 1) = (3x + 1)(x - 2)

=> 2(3x + 1)2 - (3x + 1)(x - 2) = 0

=> (3x + 1)(6x + 2 - x + 2) = 0

=> (3x + 1)(5x +4 ) = 0

=> \(\orbr{\begin{cases}3x+1=0\\5x+4=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=-\frac{1}{3}\\x=-\frac{4}{5}\end{cases}}\)

c) 27x2(x + 3) - 12(x2 + 3x) = 0

=> 27x2(x + 3) - 12x(x + 3) = 0

=> 3x(9x - 4)(x + 3) = 0

=> 3x = 0

9x - 4 = 0

 x + 3 = 0

=> x = 0

x = 4/9

 x = -3

d) 16x2 - 8x + 1 = 4(x + 3)(4x - 1)

=> (4x - 1)2 - 4(x + 3)(4x - 1) = 0

=> (4x - 1)(4x - 1 - 4x - 12) = 0

=> 4x - 1 = 0

=> x = 1/4

6 tháng 8 2016

a) \(\left(3x-4\right)^3=\left(9x-8\right)\left(3x^2-8\right)\)

\(\Leftrightarrow27x^3+108x^2+144x+64=27x^3-72x-24x^2+64\)

\(\Leftrightarrow27x^3+108x^2+144x+64-27x^3+72x+24x^2-64=0\)

\(\Leftrightarrow132x^2+216x=0\)

\(\Leftrightarrow12x\left(11x+18\right)=0\)

\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\11x+18=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x=-\frac{18}{11}\end{array}\right.\)

 

b)  ta có  \(\left(4x-5\right)^3-\left(2x+5\right)\left(16x^2-25\right)=0\)

        \(\left(4x-5\right)^3-\left(2x+5\right)\left(4x+5\right)\left(4x-5\right)=0\)

    \(\left(4x-5\right)\left[\left(4x-5\right)^2-\left(2x+5\right)\left(4x+5\right)\right]=0\)

 \(\left(4x-5\right)\left(16x^2-40x+5^2-8x^2-10x-20x-5^2\right)=0\)

   \(\left(4x-5\right)\left(8x^2-70x\right)=0\)

=> \(\orbr{\begin{cases}4x-5=0\\8x^2-70x=0\end{cases}=>\orbr{\begin{cases}4x=5\\x\left(8x-70\right)=0\end{cases}< =>}\orbr{\begin{cases}x=\frac{5}{4}\\\orbr{\begin{cases}x=0\\8x-70=0=>x=\frac{35}{4}\end{cases}}\end{cases}}}\) \(\orbr{\begin{cases}4x-5=0\\8x^2-70x=0\end{cases}< =>\orbr{\begin{cases}x=\frac{5}{4}\\x\left(8x-70\right)=0\end{cases}\orbr{\begin{cases}x=\frac{5}{4}\\\orbr{\begin{cases}x=0\\8x-70=0=>x=\frac{35}{4}\end{cases}}\end{cases}}}}\)

\(\orbr{\begin{cases}4x-5=0\\8x^2-70x=0\end{cases}=>\orbr{\begin{cases}x=\frac{5}{4}\\x\left(8x-70\right)=0\end{cases}}}\)

=> \(\orbr{\begin{cases}x=0\\x=\frac{35}{4}\end{cases}}\)     Vậy   \(\orbr{\begin{cases}x=\frac{5}{4}\\x=0\end{cases}}\) hoặc   \(x=\frac{35}{4}\)

NV
16 tháng 10 2019

\(A=\left(5x\right)^2-1^2=\left(5x-1\right)\left(5x+1\right)\)

\(B=\left(x-2\right)^2-y^2=\left(x-y-2\right)\left(x+y-2\right)\)

\(C=x\left(x^2+8x+16\right)=x\left(x+4\right)^2\)

\(D=\left(x-y\right)\left(x+y\right)-3\left(x+y\right)=\left(x-y-3\right)\left(x+y\right)\)

\(E=\left(3x\right)^2-\left(y^2-10y+25\right)=\left(3x\right)^2-\left(y-5\right)^2\)

\(=\left(3x-y+5\right)\left(3x+y-5\right)\)

\(F=x^2+x+7x+7=x\left(x+1\right)+7\left(x+1\right)=\left(x+1\right)\left(x+7\right)\)

\(G=3x^2+3x-5x-5=3x\left(x+1\right)-5\left(x+1\right)=\left(x+1\right)\left(3x-5\right)\)

\(H=x^2+x-5x-5=x\left(x+1\right)-5\left(x+1\right)=\left(x-5\right)\left(x+1\right)\)